Optical soliton solutions of the pulse propagation generalized equation in parabolic-law media with space-modulated coefficients - İnç, Mustafa; Kilic, Bulent; Baleanu, Dumitru (Elsevier Gmbh, 2016)
In this paper, the Riccati equation is used to construct the soliton solutions for pulse propagation equation with z-dependent coefficients. The periodic wave and the optical soliton solutions are obtained for the pulse propagation equation with dependent coefficients. We show that the examined dependent coefficients effected the terms of equation's velocity. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Pulse propagation equation with; z-dependent coefficients; Riccati equation; Optical soliton